A prospective study on the efficacy of sequential treatment of technology lipido-colloid impregnated with silver and technology lipido-colloid nano-oligosaccharide factor in the management of venous leg ulcers - Wong, Natalie Shi Qi (2024)
Background and Aims: Venous leg ulcers (VLUs) are associated with significant morbidity and poor quality of life (QOL). Compression therapy and wound dressing are the mainstay treatment options. Technology Lipido-Colloid Impregnated with Silver (TLC-Ag) reduces bacterial load and Technology Lipido-Colloid Nano-Oligosaccharide Factor (TLC-NOSF) reduces elevated matrix metalloproteinases and improve wound healing. However, evidence is scarce on the role of sequential therapy. This study aims to evaluate if sequential treatment with TLC-Ag and TLC-NOSF improves VLU wound healing and QOL. Methods: This is a prospective cohort study from May 2020 to October 2021 on patients with VLUs who received sequential therapy, consisting of 2 weeks of TLC-Ag followed by two-layer compression bandage (2LB) with TLC-NOSF until complete wound healing. Participants were followed-up with weekly dressing changes. Our primary outcomes were wound area reduction (WAR) and Pressure Ulcer Scale of Healing (PUSH) score. Our secondary outcomes were QOL measures. Results: There were 28 patients with 57.1% males (n = 16) with a mean age of 65.3 years. Mean duration of VLU was 13.9 ± 11.7 weeks before the initiation of sequential therapy. Mean baseline wound area was 8.44 cm2. Median time to wound healing was 10 weeks. 57.1% of patients achieved complete wound closure at 3 months. There was significant WAR after 1 month (mean area 8.44–5.81 cm2, 31.2% decrease) and after 3 months (mean area 8.44–2.53 cm2, 70.0% decrease). Mean monthly WAR was 28.9%. PUSH score also decreased at 1 month (16.5% decrease, p < 0.001) and 3 months (63.3% decrease, p < 0.001) marks following the sequential therapy. EuroQol Visual Analog Scale (EQ-VAS) improved following sequential therapy (baseline: 69.0 ± 15.0, week 13: 80.2 ± 13.2, p < 0.001). Conclusion: Sequential therapy with TLC-Ag followed by TLC-NOSF and 2LB is feasible, with good wound healing and improvement in QOL of patients with VLUs.